Application of Refill, Recoil, Rebound (3R) as a Novel Chest Compression Technique in Cardiopulmonary Resuscitation; Report of Two Cases - Tsoungani , Georgia; Nour, Sayed (Archives of Academic Emergency Medicine, 2025)
Cardiopulmonary resuscitation (CPR) remains controversial with dismal outcomes for cardiac arrest (CA) victims. Inadequate organ perfusion and frequent CPR-related trauma most likely occur due to inappropriate adaptation to hemostatic conditions, electrophysiology, cardiotorsal anatomy, and thoracic biomechanics. Alternatively, we propose a new technique compromising chest compressions through the 5th intercostal space while placing the victim in the left lateral decubitus position with wrapped abdomen and raised legs, allowing to: bypass the sternal barrier, refill the heart, and then recoil-rebound the chest (3R /CPR), within the axis of the cylindrical ribcage. Our goal is to evaluate the technique following its necessary application on two drowning victims. It seems that, 3R/CPR adapts the pathophysiological conditions of CA victims promoting a less traumatic return of spontaneous circulation (ROSC), making it worthy of further investigation and study.